EFEK HARGA, DISKON, DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN DENGAN VARIASI PRODUK SEBAGAI VARIABEL MODERASI - Kusnadi, Ali; Firmansyah, Fani (Universitas Bina Taruna Gorontalo, 2025)
The purpose of this study is to investigate how Metro Swalayan customers' purchase decisions are influenced by pricing, promotions, and amenities, which are in turn influenced by product variations. Nowadays, a lot of individuals desire their requirements to be addressed promptly and efficiently. As a result, a lot of individuals would rather buy at supermarkets to satisfy their necessities. This study's research methodology is quantitative. With a sample size of 100 responders, the population is infinite and includes all Metro Swalayan Malang customers. The sampling procedure employs the accidental sampling strategy, which is a non-probability approach. A questionnaire is used in the data collection process, and the Partial Least Square (PLS) method is used to test the results using SmartPLS 4 software. The study's findings indicate that (1) pricing significantly influences consumers' decisions to buy. (2) Purchase decisions are not much impacted by discounts. (3) Purchase decisions are not much impacted by facilities. (4) The impact of price on purchasing decisions cannot be moderated by product variety. (5) The impact of discounts on purchasing decisions cannot be moderated by product variety. (6) The impact of facilities on purchasing decisions cannot be moderated by product variety..